Rhetorical Move Structures in Research Article Abstracts: A Comparative Genre Analysis of Local and International Publications - Maribel Belleza (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
Modern scholarship recognizes the research abstract structures in the form of academic texts as disciplinary and communicative genres (Hassan & Siddique, 2026). Recognizing this complexity, and the limited study on how rhetorical patterns vary across different publication settings, this study investigates rhetorical move patterns to address common abstract writing errors identified by Hurley (2025). Employing a mixed-methods approach, the research utilizes Hyland’s (2000) Move Structure Framework to analyze 200 abstracts, comparing 100 local and 100 international research abstracts from reputable international journals published. The findings reveal that Hyland’s IPMRC (Introduction, Purpose, Methodology, Product/Result, Conclusion) model is the dominant pattern across both groups of local and international research abstracts. Statistical analysis identifies Purpose, Methodology, Result, and Conclusion as obligatory moves, while the Introduction remains optional. Comparative data using Log-likelihood tests shows a significant difference in move frequency. International abstracts recorded a frequency of 416 (pmw=21614.88), while local abstracts recorded 402 (pmw=17407.12). The resulting Log-likelihood value (LL = 9.58, p < 0.01) indicates that international researchers employ rhetorical moves with significantly greater frequency and consistency than their local counterparts. Pedagogically, these results underscore the value of genre analysis in the classroom. Explicitly teaching rhetorical structures enables students to: 1) Compose well-structured, professional abstracts, 2) Benefit from refined, discourse-focused writing instruction and 3) Gain a comprehensive grasp of the broader research body. Ultimately, this study recommends that academic writing curricula explicitly integrate rhetorical move analysis to empower language learners in producing high-impact research abstracts.